Evaluation of inhibitors of intestinal UDP-glucuronosyltransferases 1A8 and 1A10 using raloxifene as a substrate in Caco-2 cells: Studies with four flavonoids of Scutellaria baicalensis. (April 2021) - Chang, Che-Fu; Chang, Yu-Ching; Lin, Jing-Tang; Yu, Chen-Wei; Kao, Yu-Ting
Abstract: UDP glucuronosyltransferases (UGTs) of the gastrointestinal tract play a crucial role in protection against the toxic effects of xenobiotics in the environment. UGTs such as UGT1A8 and UGT1A10 are predominantly expressed in gastrointestinal tissues. In this study, we examined the phase II metabolism of raloxifene in differentiated Caco-2 monolayers by inducing UGT1A8 and UGT1A10 expression in these cells. The present study evaluated the following four flavonoids of Scutellaria baicalensis as model herbal compounds: scutellarein, salvigenin, baicalein, and wogonin. All test compounds, endpoint substrates, and their metabolites were quantified using liquid chromatography and high-resolution mass spectrometry. The transepithelial electrical resistance values for the individual compounds were comparable regardless of whether they were measured individually. Salvigenin significantly inhibited UGT1A8 and UGT1A10 activities in a concentration-dependent manner. All individual compounds except scutellarein inhibited UGT1A8 and UGT1A10 activity at a concentration of 100 μM. In addition, all individual flavonoids at 100 μM, except wogonin, significantly increased the amount of raloxifene in the basolateral chambers. The positive control, canagliflozin, significantly inhibited both UGT1A8 and UGT1A10 activities. These findings suggest that the Caco-2 assay can be utilized for identifying UGT1A8 and UGT1A10 inhibitors and indicate the potential of salvigenin for enhancing the pharmacological effects of UGT substrate drugs. Graphical abstract: Unlabelled Image Highlights: Intestinal UDP-glucuronosyltransferases 1A8 and 1A10 metabolize drugs and toxins. Salvigenin, from Scutellaria baicalensis, significantly inhibits these enzymes. Such inhibition could alter bioavailability of co-administered substrate drugs. Our rapid screening assay can identify other inhibitors of these enzymes. The assay can predict potential herb–drug interactions.